Development of An Educational Board Game on Storyboarding to Enhance Learning Achievement in The Digital Media Production Course for Vocational Certificate Grad 3 Students - Kaewkaithai, Krittanai; Srangkaew, Apiwat; Chaisiriyanon, Paratthakorn; Abdulloh, Surapong (Journal of Innovation and Management, 2025)
This research aimed to: (1) develop an educational board game on “Storyboarding” to enhance the learning achievement of vocational certificate (Grade 3) students in the Digital Media Production course, (2) compare students’ pre- and post-learning achievement using the educational board game, and (3) examine students’ satisfaction with learning through the board game. The research instruments included the educational board game, a learning achievement test, a media quality assessment form, and a student satisfaction questionnaire. Data were analyzed using descriptive statistics: mean, standard deviation and t-test to compare pre- and post-test scores. The results revealed that: (1) the developed educational board game was evaluated to be of “very good” quality in terms of both content and media; (2) students’ learning achievement improved significantly after using the board game. The mean pre-test score was 10.27, while the mean post-test score was 17.60, indicating a statistically significant increase in learning outcomes; and (3) students’ satisfaction with the board game was at a “high” level, with an average score of 4.08.